Physiological Data-Based Evaluation of a Social Robot Navigation System - Kivrak, Hasan; Uluer, Pinar; Kose, Hatice; Gumuslu, Elif; Barkana, Duygun Erol; Cakmak, Furkan; Yavuz, Sirma (IEEE, 2020)
The aim of this work is to create a social navigation system for an affective robot that acts as an assistant in the audiology department of hospitals for children with hearing impairments. Compared to traditional navigation systems, this system differentiates between objects and human beings and optimizes several parameters to keep at a social distance during motion when faced with humans not to interfere with their personal zones. For this purpose, social robot motion planning algorithms are employed to generate human-friendly paths that maintain humans' safety and comfort during the robot's navigation. This paper evaluates this system compared to traditional navigation, based on the surveys and physiological data of the adult participants in a preliminary study before using the system with children. Although the self-report questionnaires do not show any significant difference between navigation profiles of the robot, analysis of the physiological data may be interpreted that, the participants felt comfortable and less threatened in social navigation case.
Keywords: social navigation; personal zone; HRI; emotion recognition; deeplearning; physiological data; RECOGNITION; Computer Science; Engineering; Robotics